From phosphine-stabilised towards naked Au8 clusters through ZIF-8 encapsulation. Issue 11 (17th September 2021) - Kollmannsberger, Kathrin L.; Weger, Kathrin; Kratky, Tim; Günther, Sebastian; Tomanec, Ondřej; Warnan, Julien; Fischer, Roland A.
Abstract : The encapsulation of phosphine-stabilised Au8 clusters in ZIF-8 is presented as a confining and stabilising strategy. This enables ligand stripping without triggering gold particle agglomeration or loss of atom-precision. Abstract : In contrast to the corresponding inert bulk material, nanoscale gold clusters bear remarkable optical and catalytic properties that are highly dependent on the cluster size. Metal–organic frameworks (MOFs) have recently been identified as attractive host matrices for metallic clusters due to their confining porous environment. Through the rational choice of sulfonated ligands, we report the first encapsulation of a phosphine-stabilised Au8 cluster into ZIF-8 via a bottle-around-ship approach. The cluster integrity within the MOF was proven by thorough characterisation including diffuse reflectance UV-visible spectroscopy and high-resolution transmission electron microscopy with elemental mapping. This strategy enabled precise control of cluster loadings from low (1.1 wt% Au) to high (8.2 wt% Au) values. The stabilising effect provided by the MOF was further analysed in temperature-dependent studies that revealed no cluster agglomeration up to 350 °C in vacuo . Furthermore, stable, confined Au clusters were produced via an original atomicity-preserving ligand-stripping procedure by taking advantage of phosphine oxidation. Thus, capitalising on ZIF-8 hosting ability for metal nanoclusters while exploiting confined space for activation delivers a promising way towards producing and studying atom-precise clusters.